Integral estimates of the solutions of fractional-like equations of perturbed motion - Martynyuk, Anatoliy; Stamov, Gani; Stamova, Ivanka (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, the results of the analysis of nonlinear systems with fractional-like derivatives of the state vector are presented. Using the method of integral inequalities, some estimates of the solutions are obtained, and criteria for Heyers–Ulam–Rassias stability of a fractional-like scalar equation are established.